2000
DOI: 10.1103/physrevc.63.014002
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic contributions to the deuteron photodisintegration in the Bethe-Salpeter formalism

Abstract: In plane wave one-body approximation the reaction of deuteron photodisintegration is considered in the framework of the Bethe-Salpeter formalism for two-nucleon system. Results are obtained for deuteron vertex function, which is the solution of the homogeneous Bethe-Salpeter equation with a multi-rank separable interaction kernel, with a given analytical form. A comparison is presented with predictions of non-relativistic, quasipotential approaches and the equal time approximation. It is shown that important c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The model has no final-state interactions or explicit nucleon resonance contributions. There is also a relativistic calculation of photodisintgration in Born approximation using the Bethe-Salpeter formalism [182,183]. It is found that the cross section is a factor of 2 to 10 times too small, and that relativistic effects are large.…”
Section: Cross-section and Polarization Observablesmentioning
confidence: 99%
“…The model has no final-state interactions or explicit nucleon resonance contributions. There is also a relativistic calculation of photodisintgration in Born approximation using the Bethe-Salpeter formalism [182,183]. It is found that the cross section is a factor of 2 to 10 times too small, and that relativistic effects are large.…”
Section: Cross-section and Polarization Observablesmentioning
confidence: 99%